Comparison of the Corrosion Behaviour of the Re-cast Aluminium 5083 and Its Bulk Alloy - Zakiah Kamdi; Loo Yuen Hern; Saliza Azlina Osman; Nur Azam Badarulzaman; Tay Sin Kiat (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
Aluminium alloys are widely used in various industries due to their excellent properties. In industry, corrosion is always an issue that engineers are mainly concerned. This study will characterise and analyse the corrosion behaviour of the aluminium 5083 bulk alloy, aluminium 5083 machining chip and mixture of aluminium 5083 (bulk alloy and machining chip). The machining chips were melted at 750ºC and re-cast using sand casting. The samples were characterised using Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), and X-ray diffraction Analysis (XRD). SEM revealed the presence of fusion voids and insoluble phases in the re-cast machining chips. At the same time, EDS identified the presence of oxygen and carbon, indicating the formation of Al2O3 and carbides during the sand-casting process. XRD showed peaks corresponding to aluminium magnesium and aluminium silicon. The potentiodynamic polarisation test was performed with a polarisation scan rate of 2 mV/s and a potential range of -1.5 V to 1.5 V, using a saturated Ag/AgCl reference electrode, aluminium samples as the working electrode, and a platinum sheet as the counter electrode. The aluminium 5083 bulk alloy exhibited the lowest corrosion rate (0.88 mm/year), followed by the mixture of aluminium 5083 (bulk alloy and machining chip) (2.15 mm/year), and the aluminium 5083 machining chip (2.93 mm/year). The characterisation of the specimen shows the corrosion product and corrosion pit occur after the corrosion test. These results highlight the superior corrosion resistance of the bulk alloy compared to the machining chip or the mixture.